“BUSINESS AS UNUSUAL”:PANDEMIC CONCENTRATION OF EXECUTIVE POWERS IN CROATIA - Gardašević, Đorđe (Pravni zapisi, 2021)
Faced with the Covid-19 pandemic, countries around the globe responded with a wide range of special measures. Whereas some of them resorted to their constitutional emergency rules, others opted to act through legislation. The author argues that the effects of the legislative approach to the epidemic in Croatia actually resemble the state of an emergency in the proper sense of the word, although the authorities try to present the whole case as a situation of “legal normalcy”. More precisely, the author claims that in practice the adopted model produces concentration of power in the executive branch far beyond what one could expect in ordinary times. To prove that, the author analyses the Croatian legal anti-epidemic framework through several elements (declaration of emergency, law-making powers, overview of executive emergency actions, parliamentary sittings). Finally, the author argues that the constitutional state of natural disaster in Croatia should have been proclaimed.
Keywords: Covid-19; pandemic; epidemic; states of emergency; Croatia